Cost-effectiveness analysis of oxycodone with naloxone versus oxycodone alone for the management of moderate-to-severe pain in patients with opioid-induced constipation in Canada. (3rd March 2016) - Goeree, Ron; Goeree, Jeff
Abstract: Background: Approximately 20–30% of Canadians suffer from chronic pain. Guidelines for the management of chronic pain support the use of controlled-release (CR) opioids to treat chronic pain. Although effective in managing chronic pain, oxycodone is associated with high rates of opioid-induced constipation (OIC). The cost-effectiveness of a combination of oxycodone for the management of pain and naloxone for the relief of OIC has not previously been evaluated for Canada. Methods: A decision analytic model was developed to estimate the cost-utility of combination oxycodone/naloxone compared to oxycodone alone in four populations. Drug costs for managing pain and healthcare costs related to managing OIC were included in the analysis and the primary measure of effectiveness was quality adjusted life years (QALYs) derived from OIC rates observed in clinical trials. The analysis was conducted from a healthcare system perspective, used a 1-year time horizon, and results were expressed in 2015 Canadian dollars. Results: In all four patient populations, there was a trade-off between slightly higher total expected costs for Targin treated patients compared to oxycodone treated patients, but also improved clinical benefits in terms of reduced OIC, which resulted in higher QALYs for patients. Although analgesic costs were found to be slightly higher for Targin treated patients, Targin also resulted in cost offsets to the healthcare system in terms of less rescue laxative drug use and other resources required for the management of OIC. The resulting 1-year cost-utility of Targin compared to oxycodone ranged from $2178–$7732 per QALY gained in the base case analysis, and it was found that these cost-utility results remained robust and at low values throughout a series of one-way deterministic analyses of uncertainty. Conclusion: The clinical effectiveness of oxycodone/naloxone in managing pain and OIC compared to CR oxycodone alone resulted in low cost-utility estimates.